Deciphering the molecular effects of romidepsin on germ cell tumours: DHRS2 is involved in cell cycle arrest but not apoptosis or induction of romidepsin effectors. Issue 1 (20th November 2018) - Nettersheim, Daniel; Berger, Daniel; Jostes, Sina; Skowron, Margaretha; Schorle, Hubert
Abstract: Testicular germ cell tumours (GCTs) mostly affect young men at age 17‐40. Although high cure rates can be achieved by orchiectomy and chemotherapy, GCTs can still be a lethal threat to young patients with metastases or therapy resistance. Thus, alternative treatment options are needed. Based on studies utilising GCT cell lines, the histone deacetylase inhibitor romidepsin is a promising therapeutic option, showing high toxicity at very low doses towards cisplatin‐resistant GCT cells, but not fibroblasts or Sertoli cells. In this study, we extended our analysis of the molecular effects of romidepsin to deepen our understanding of the underlying mechanisms. Patients will benefit from these analyses, since detailed knowledge of the romidepsin effects allows for a better risk and side‐effect assessment. We screened for changes in histone acetylation of specific lysine residues and analysed changes in the DNA methylation landscape after romidepsin treatment of the GCT cell lines TCam‐2, 2102EP, NCCIT and JAR, while human fibroblasts were used as controls. In addition, we focused on the role of the dehydrogenase/reductase DHRS2, which was strongly up‐regulated in romidepsin treated cells, by generating DHRS2 ‐deficient TCam‐2 cells using CRISPR/Cas9 gene editing. We show that DHRS2 is dispensable for up‐regulation of romidepsin effectors ( GADD45B, DUSP1, ZFP36, ATF3, FOS, CDKN1A, ID2 ) but contributes to induction of cell cycle arrest. Finally, we show that a combinatory treatment of romidepsin plus the gluccocorticoid dexamethasone further boosts expression of the romidepsin effectors and reduces viability of GCT cells more strongly than under single agent treatment. Thus, romidepsin and dexamethasone might represent a new combinatorial approach for treatment of GCT.